1990
DOI: 10.1016/0014-5793(90)81497-c
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of benzoquinones with mitochondria interferes with oxidative phosphorylation characteristics

Abstract: Studies with four benzoquinones, viz. juglone, embelin, maesaquinone and maesanin, on rat liver mitochondria oxidative phosphorylation have been carried out. Three of the benzoquinones are uncouplers in the order juglone > maesoquinone > embelin, while maesanin is an inhibitor of electron transport and oxidative phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…However, previous biochemical studies have shown that benzoquinones including embelin can act as uncouplers of the mitochondrial membrane potential (MMP; Makawiti et al , ). We therefore measured changes in the MMP in response to increasing embelin concentrations and found that proliferating ECs were readily depolarized by low concentrations of embelin, whereas quiescent ECs and tumor cells were not readily uncoupled (Fig A and B and ).…”
Section: Resultsmentioning
confidence: 99%
“…However, previous biochemical studies have shown that benzoquinones including embelin can act as uncouplers of the mitochondrial membrane potential (MMP; Makawiti et al , ). We therefore measured changes in the MMP in response to increasing embelin concentrations and found that proliferating ECs were readily depolarized by low concentrations of embelin, whereas quiescent ECs and tumor cells were not readily uncoupled (Fig A and B and ).…”
Section: Resultsmentioning
confidence: 99%
“…However, earlier investigations reported that maesanin possesses non-specific host defense stimulatory and anti-5-LO activities (Kubo et al, 1987;Fukuyama et al, 1993), and it also inhibits the mitochondrial oxidative phosphorylation (Makawiti et al, 1990). In addition, recent investigations have reported on the antiviral, haemolytic and molluscicidal activities of triterpenoid saponins, isolated from leaves of this plant 2001).…”
mentioning
confidence: 97%
“…Because these plant-derived compounds have antibacterial, antifungal, and antiamoebic properties, they are of potential pharmacological use (1). The eventual application of any compound, however, depends on the results of toxicological tests performed to evaluate possible deleterious effects on host organisms as well as on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with isolated rat liver mitochondria indicate that some benzoquinones (e.g., maesanin) inhibit respiration and that others (e.g., MAQ, embelin, and juglone) potently uncouple mitochondrial electron transfer from phosphorylation (1,3). Makawiti et al (1) have suggested that the uncoupling effect of MAQ and embelin in rat liver may account for the observed inhibition of respiration in cow pea. Such an explanation is not intuitively obvious, however, and we have therefore studied the effect of one of these compounds (MAQ) on respiration in plant mitochondria.…”
Section: Introductionmentioning
confidence: 99%